European Union Public Law Text and Materials - Chalmers, Damian (Cambridge University Press, 2013)
This book reprints the first ten chapters of the wider project European Union Law: Text andMaterials (CambridgeUniversity Press, 2006) thatwe co-wrotewith Christos Hadjiemmanuil and Giorgio Monti. We would like to thank them for their support for this book. We decided to publish these chapters as a separate book partly as a response to a perceived demand by those who wish to study only the public law of the European Union. We also decided to publish them separately as they bring out issues which are present in all European Union law but are more openly contested in its public law.